Cytotoxic Activity of Chromolaena odorata Ethyl Acetate Fraction and Its Inhibitory Mechanism Through Cell Cycle Modulation Against WiDr Colon Cancer Cells - Hasnawati Hasnawati; Asniar Pascayantri; Dian Munasari Solo; Nurramadhani A. Sida; Wa Ode Nurhayati Basri; Sarida Sarida; Aisyah Aisyah; Nurul Azizah Putri Herina; Muhammad Bagas Rahya Arafat (Jurnal Kartika Kimia, 2026)
Chromolaena odorata has traditionally been used to treat various diseases such as bacterial and fungal infections, external wounds, stomach ulcers, and vomiting blood. Its anticancer activity has been extensively studied. This study aims to prove the cytotoxic effect of Chromolaena odorata leaves on WiDr colon cancer cells and its inhibitory mechanism through cell cycle modulation. Dried Chromolaena odorata leaves were extracted by maceration using 96% ethanol. They were then triturated with n-hexane and ethyl acetate to obtain n-hexane and ethyl acetate fractions. The ethyl acetate fraction was then screened for phytochemicals using the tube method and tested for cytotoxicity using the MTT assay. The selectivity index (SI) was calculated by comparing the IC50 of WiDr cells to Vero cells. Cell cycle modulation was then observed using flow cytometry. The results showed that the ethyl acetate fraction of Chromolaena odorata leaves contained flavonoids, phenolics, and tannins, and was moderately cytotoxic to WiDr cells with an IC50 of 207.69 µg/mL,, with an SI of 3.5. The ethyl acetate fraction of Chromolaena odorata was able to inhibit the growth of WiDr colon cancer cell division through the G2/M and Sub G1 phases. Thus, it was concluded that the ethyl acetate fraction of Chromolaena odorata has great potential to be developed as a candidate source of colon anticancer agents.